2011
DOI: 10.1108/00220411111109449
|View full text |Cite
|
Sign up to set email alerts
|

Enabled backchannel: conference Twitter use by digital humanists

Abstract: PurposeTo date, few studies have been undertaken to make explicit how microblogging technologies are used by and can benefit scholars. This paper investigates the use of Twitter by an academic community, and poses the following questions: does the use of a Twitter enabled backchannel enhance the conference experience, collaboration and the co-construction of knowledge? How is microblogging used within an academic conference setting, and can we articulate the benefits it may bring to a discipline? Prominent Twe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
179
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(195 citation statements)
references
References 38 publications
10
179
2
4
Order By: Relevance
“…A number of other researchers have pointed to Twitter being used at conferences. 3,4 In order to share images and videos, 69% of researchers who did so used YouTube, 14% used SlideShare, and 12% Flickr. Obviously, these three tools have three different applications.…”
mentioning
confidence: 99%
“…A number of other researchers have pointed to Twitter being used at conferences. 3,4 In order to share images and videos, 69% of researchers who did so used YouTube, 14% used SlideShare, and 12% Flickr. Obviously, these three tools have three different applications.…”
mentioning
confidence: 99%
“…Priem and Costello (2010) studied whether and how scholars cite on Twitter by interviewing scholars and analysing their tweets. Their study showed the relevance of Twitter for researchers beyond conferences (as pointed out by Ross et al, 2011) and therefore substantiated the need for more holistic analyses of how researchers use Twitter. Weller et al (2011) focused on tweets containing conference-related hashtags and extended the view of Twitter citations introduced by Priem and Costello (2010) to retweets and mentions.…”
Section: Twitter Usage By Researchersmentioning
confidence: 99%
“…Ross et al (2011) described Twitter as an ideal medium to establish a "more participatory conference culture" by expanding communication and participation. Consequently, Twitter usage during academic conferences is the focal point of several analyses (Ebner, 2009;Letierce et al, 2010;Weller et al, 2011;Wen et al, 2014).…”
Section: Twitter Usage By Researchersmentioning
confidence: 99%
See 1 more Smart Citation
“…Others state that the use of SNS is deeply related to civic engagement (Brandtzaeg and Heim, 2011) or to spread information about conferences (Ross, et al, 2011).…”
Section: The First Hypothesis Claims That Communications Faculty Use mentioning
confidence: 99%